Maintenance and Operations and the School Business Administrator - School Business Officials Int'l, Association of (Rowman & Littlefield Publishers, 2003)
Every aspect of maintenance and operations is covered in this compilation of information-packed articles from School Business Affairs. Articles cover topics ranging from contracting out and the environment to energy and safety issues.